2019
DOI: 10.15835/nbha47311433
|View full text |Cite
|
Sign up to set email alerts
|

Priming with Vitamin U Enhances Cold Tolerance of Lettuce (Lactuca sativa L.)

Abstract: Priming may be an efficient pre-treatment of plants in order to enhance their ability to cope with unfavourable growth conditions, and to improve defensive metabolism through elevated levels of protective substances which may also act as health-promoting agents upon human consumption. The aim of this work was to evaluate the beneficial influence of priming with the naturally occurring, but scarcely known vitamin U (S-methylmethionine) on cold stress tolerance of lettuce (the frequently grown ‘May King’ cultiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
(38 reference statements)
1
7
0
Order By: Relevance
“…This may be a simple and effective way to overcome the negative impacts of high soil salinity on germination and on the vigor of new plantlets (Tabasssum et al 2017). Similar results were reported for lettuce seeds, in which cold tolerance during germination and seedling establishment was enhanced with pre-treatment using 0.25 mM and 2.0 mM SMM (Fodorpataki et al 2019). Seed priming was also achieved with a sequential pre-treatment with triacontanol and ascorbate, resulting in improved germination index and reduced germination time of wheat grains exposed to salt stress (Mahboob et al 2019).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This may be a simple and effective way to overcome the negative impacts of high soil salinity on germination and on the vigor of new plantlets (Tabasssum et al 2017). Similar results were reported for lettuce seeds, in which cold tolerance during germination and seedling establishment was enhanced with pre-treatment using 0.25 mM and 2.0 mM SMM (Fodorpataki et al 2019). Seed priming was also achieved with a sequential pre-treatment with triacontanol and ascorbate, resulting in improved germination index and reduced germination time of wheat grains exposed to salt stress (Mahboob et al 2019).…”
Section: Discussionsupporting
confidence: 72%
“…Previous studies demonstrated that addition of micromolar or millimolar concentrations of SMM to the nutrient solution contributed to the tolerance of hypoxia, of mosaic virus infection, of heavy metal toxicity and of low temperature in certain crop species (Paldi et al 2014). Its utility as a priming agent was reported only in lettuce plants exposed to cold stress and to high salinity, where it also increased the healthpromoting properties of fresh leaves (Fodorpataki et al 2016(Fodorpataki et al , 2019. All these studies lead to the idea that exogenous supplementation of SMM may promote plants' growth and development under environmental stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A scarcely studied vitamin is S-methylmethionine (vitamin U). It is produced by all angiosperms, since it is involved in their sulphur metabolism ( Ludmerszki et al, 2014 ; Fodorpataki et al, 2019 ). In fact, its role in the biosynthesis of sulfopropionates (osmoprotectants) and polyamines is valuable for plant resistance ( Ludmerszki et al, 2014 ).…”
Section: Amino Acids and Other N -Containing Compomentioning
confidence: 99%
“…It was highly effective in protecting maize against cold stress, by stimulating the phenylpropanoid pathway, increasing the content of phenol derivatives and anthocyanins, and protecting the photosynthetic apparatus ( Páldi et al, 2014 ). Priming lettuce with this vitamin resulted in a greater tolerance to cold, improving its germination, photosynthetic efficiency, and content of carotenoids and vitamin C ( Fodorpataki et al, 2019 ).…”
Section: Amino Acids and Other N -Containing Compomentioning
confidence: 99%
“…Another compound from this family is S-methylmethionine (vitamin U), produced by all angiosperms. Treating plants with it to enhance cold tolerance has been studied [ 101 , 102 ], but to date its application against salt or drought stress has not been.…”
Section: Naturally Accumulated Plant Osmoprotectantsmentioning
confidence: 99%